Assessment of Nutritional Status and Oral frailty among Geriatric population using different Dental prosthesis: An observational study - Tadas, Sharvari; Dodamani, Arun; Vishwakarma, Prashanth; Kumbhargave, Pooja; Gadekar, Ankita; Wankhede, Saloni (Journal of Nepalese Prosthodontic Society, 2026)
Introduction: Oral frailty is increasingly recognized as an early indicator of systemic frailty and adverse health outcomes in older adults. Compromised oral function may restrict dietary intake and negatively influence nutritional status. Therefore, the present study aimed to assess the nutritional status and oral frailty among geriatric individuals rehabilitated with different types of dental prostheses. Methods: This analytical cross-sectional study included 96 geriatric participants aged ≥60 years rehabilitated with dental prostheses for at least three months. Participants were stratified into five groups: complete denture, removable partial denture, fixed partial denture, overdenture, and full mouth rehabilitation. Oral frailty was assessed using a validated questionnaire. Nutritional status was evaluated using a multiple-pass 24-hour dietary recall method and anthropometric measurements. Nutrient intake was also assessed. Data were entered into Microsoft Excel and analyzed using SPSS version 23. Results: No significant association was observed between prosthesis type and body mass index (p > 0.05). Energy and macronutrient intake were comparable across prosthetic groups. However, calcium intake differed significantly, with the lowest intake observed among full mouth rehabilitation users (p = 0.044). Perceived oral impact scores varied significantly between prosthetic groups (p = 0.033), with higher scores in the full mouth rehabilitation group. Oral frailty scores showed a highly significant difference across prosthesis types (p = 0.002), with the highest scores observed in full mouth rehabilitation users and the lowest in fixed partial denture users. Conclusion: Prosthesis type influenced oral frailty and selected nutritional parameters among geriatric individuals. Comprehensive prosthodontic care should integrate functional assessment and nutritional counselling to improve geriatric health outcomes.